The influence of 10-day proprioceptive training on the results of the FMS test in young female volleyball players – a pilot study - Ciemiński, Karol (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Effective preventive measures are necessary not only to reduce the incidence of injuries in volleyball, but also to reduce the costs caused by these injuries. Aim of Study. The aim of the study was to investigate the impact of 10-day proprioceptive training on the results of the functional movement screen FMS in young female volleyball players. Material and Methods. The study was conducted in a group of twelve female volleyball players. The training was performed daily in the form of a circuit for 10 consecutive days. The FMS test was run three times. The first two trials, in one week interval, were conducted before the start of the proprioceptive training. The third assessment was carried out after the completion of 10-day proprioceptive training. Results. The analysis showed differences between studied measurements: first and third as well as second and third (p ≤ 0.001) in the following FMS test trials: deep squat, hurdle squat, push-ups and rotational trunk stability. Based on mean values of the overall FMS test score, an improvement was observed after the application of 10-day proprioceptive training (p ≤ 0.001). The study showed that the number of asymmetries found in the FMS test decreased by 50% after the application of the training. Conclusions. The applied proprioceptive training positively influenced the number of points obtained in the FMS test. It also reduced the number of asymmetries and caused that all of the subjects obtained the total FMS test results of ≥17, which is believed to reduce the likelihood of injury. Research results indicate that proprioceptive training should be taken into account by volleyball coaches in daily training
Keywords: Functional Movement Screen, asymmetry, injuryprevention, adolescent, volleyball.; asymmetry; injury prevention; adolescent; volleyball